Physical Characteristics of Tofu Dregs Flour as a Functional Food Ingredient: Tofu Dregs Flour - Ambar, Fidyasari; Zalzabilah, Hanum; Abimanyu, J Nelson (Universitas Muhammadiyah Sidoarjo, 2026)
Tofu dreg flour is a processed product derived from wet tofu residue, which is dried either by direct sunlight or using a mechanical dryer. Before a material can be utilized as a food ingredient, its physical properties and characteristics must first be understood to determine the appropriate direction for its potential application in food development. This study aims to characterize the physical properties of soybean dreg flour, including color analysis, bulk density, water and oil absorption capacity, and flour morphology. Data analysis was conducted descriptively using a quantitative approach. The physical analysis of the soybean dreg flour showed the following results: color values of a* 2.9, b* 17.6, L* 79.6, chroma (C*) 17.8, and hue angle (h°) 80.7. The bulk density was recorded at 1.83 g/mL. The water absorption capacity was 8.00 g/g (dry basis), and the oil absorption capacity was 2.80 g/g (dry basis). Morphological observations indicated the presence of protein bodies and fibers, with no starch granules detected in the flour. In conclusion, soybean dreg flour exhibits physical characteristics that suggest its potential application as a functional food substitute in the future.